77.8k views
0 votes
How to rewrite the sum as a product of the GCF of the addends and another number

1 Answer

1 vote

Step-by-step explanation:

Suppose you have the sum P+Q, and that P and Q have a GCF of g. Then the two terms P and Q can be written as ...

  • P = g·p
  • Q = g·q

Using the distributive property, we can rewrite the sum as ...

P + Q = g·p +g·q = g(p +q) . . . . . g is the GCF; (p+q) is the other number

_____

Example:

P = 48 = 8·6

Q = 40 = 8·5

g = 8, p=6, q=5

P + Q = 48 + 40 = 8(6 +5) = 8·11

User JohnUopini
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.